The need to enhance the employability competences (knowledge, skills, autonomy, and attitudes) of undergraduates in Agriculture. Evidence from students' perceptions and employers' expectations - Nigel Yoven Armoogum; Brinda Ramasawmy; Brigitte Marie Françoise Driver (Universidad de Deusto, 2016)
The Faculty of Agriculture (FoA) (University of Mauritius) is the only tertiary Education Institution in the country providing graduate training in Agriculture with an annual enrolment of about 100-125 students. Although the relative contribution of the Agricultural sector to the economy has declined over the past decade - share to GDP: 3.0% in 2014 as compared to 6.4% in 2004[1] the introduction of new schemes in support of Bio- Farming, food processing and value-addition will attract new entrepreneurs to Agriculture. This transformation in the Agriculture sector will create new job opportunities, but has to leverage on skilled human capital. Graduates with good employability skills are of strategic importance to the FoA, in line with the government's vision to develop a knowledge-based economy. This study aimed at mapping out the set of skills, understandings and personal attributes that will increase the job prospects of the fresh graduate from FoA in Agriculture. The main research question centred on the perceptions of employers, alumni and students of the FoA, concerning the most relevant competences for the Subject Area (key general and key subject specific competences), understandings and personal attributes, which enhance the employability of graduates in Agriculture. Using semi-structured interviews, the study explored and triangulated the perceptions from four key stakeholders' perspectives, namely: a range of employers, Industry Placement Supervisors, alumni of the FoA and current students. Both quantitative and qualitative insights of the perceptions on the employability skills of FoA undergraduates were obtained from a wide range of employers from the private and public sector. An analysis of data from the interviews and responses was carried out using SPSS. The key attributes that were valued by the key stakeholders have been used to inform the 'Employability Skills Subject Area Framework', and the 'Curriculum Mapping', proposed for the degree of BSc (Hons) Agriscience and Technology of the FoA. [1] "Digest of Agricultural Statistics Mauritius," Ministry of Finance and Economic Development, http://statsmauritius.govmu.org/English/StatsbySubj/Documents/Digest/Digest%20of%20Agricultural%20Statistics%202014.pdf.